Fenomena The Great Resignation Di Sektor Pendidikan Islam: Dampaknya Pada Kualitas Tenaga Pendidik Dan Strategi Talent Management Berbasis Mutu - Kussuma, Fitdarus; Aimah, Siti (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE GREAT RESIGNATION PHENOMENON IN THE ISLAMIC EDUCATION SECTOR: ITS IMPACT ON THE QUALITY OF TEACHERS AND QUALITY-BASED TALENT MANAGEMENT STRATEGIES This study examines the phenomenon of the great resignation in the Islamic education sector as a structural problem that affects the quality of educators and the sustainability of institutional quality. The purpose of this study is to analyze the factors driving educator resignations, their impact on the stability and quality of learning, and to emphasize the urgency of implementing quality-based talent management strategies in Islamic educational institutions. The study adopts a qualitative approach using a case study design conducted at MTs Darul Jannah Muara Burnai 2. Data collection techniques include semi-structured in-depth interviews with the principal, permanent teachers, honorary teachers, former teacher and administrative staff, complemented by non-participant observation and document analysis. The data were analyzed using thematic analysis through the stages of data reduction, categorization, data display, and interpretative conclusion drawing. The findings indicate that educator resignations are triggered by structural weaknesses in human resource management, such as imbalances between workload and welfare, the absence of clear career pathways, and weak systems of reward and professional development. These conditions lead to declining staff stability and educator quality, weakening motivation and organizational commitment, and hindering the development of a quality culture. This study underscores the importance of transforming human resource management toward quality-based talent management that emphasizes welfare, organizational justice, and the long-term professional sustainability of educators.